Experimental Study on the Deterioration Rules of Anchoring Performance of Rock Mass under Different Joints Distribution - Wantao Ding; Minglei Hou; Lei Chen; Keqi Liu; Rui Chen; Yang Wang; Mingbin Wang (Advances in Civil Engineering)
In order to analyze the influence of damage caused by corrosion on anchoring performance of a rock mass with different joints, the anchored rock mass specimens with different joints distribution were prepared. An electrochemical accelerated corrosion test of specimens was carried out, and the mechanical test of them under different corrosion time was also investigated. The results showed that the pitting corrosion is the main form of the anchor bar corrosion of an anchoring rock mass with different joints, and the shape of the etch pit is reverse semi-ellipse. With the increase of pitting ratio, the ultimate bond strength and the corresponding slide distance decrease gradually. The effects of pitting ratio on the slide distance of the anchor bar in an anchored joint rock mass are insignificant, but these on the bond strength of it are significant. The bond-slide model of the anchored joint rock mass with different pitting ratios was established. The research results of this paper can provide reference for analyzing the corrosion damage of a complex anchored joint rock mass in practical engineering and a theoretical basis for the design optimization of anchoring support in the complex jointed rock mass.